What are the Challenges Encountered in Initiating Green Takaful Products as a Potential Climate Finance Tool in Sri Lanka? - Rifas Abi Huraira; Mohamed Minaz Mohamed Naushad (European Journal of Islamic Finance)
Takaful as a risk-mitigating tool plays a significant role in the modern Islamic finance landscape, since it has experienced substantial growth and expanded globally in the field of economics. The alignment of the Islamic financial sector with conventional financial market trends, while adhering to Shariah law, has contributed to the growth of Islamic finance and Economics. To attain sustainable development goals, several countries have already introduced green insurance products, and the takaful market in various countries has competitively initiated green takaful products under the climate finance concept. This study aims to explore the challenges to initiating green takaful products as a climate financial tool. The study adopts a qualitative and inductive approach, utilising interview data as the primary source of information. Thematic analysis was employed to analyse the collected data for the study. The findings indicate numerous challenges, such as regulation, risk, cultural, and learning and development challenges in implementing green takaful in the Sri Lankan takaful market. This research holds a significant contribution to the takaful sector in terms of initiating green takaful products in the insurance market in Sri Lanka. Furthermore, each challenge discussed in this study and the ways to overcome them can be a major focus in future studies. Hence, it provides valuable insights for policymakers, regulatory authorities, product creators, practitioners and coming researchers in climate finance and green takaful schemes.